Organiziranje dela na domu - Scortegagna Kavčnik, Nina (Delavci in delodajalci, 2020)
The paper deals with the legal regulation of organizing home work and highlights open practical issues. Home work flourished over a period of time, mainly due to the declared epidemic. Even without this, the share of workers working from home is increasing. At the same time, we cannot overlook the legal requirements that must be met by both the employee and the employer. The labor law aspect and the aspect of safety and health at work are especially important. However, many open questions remain, such as the content of the notification to the inspectorate, the amount of compensation due to the employee for the use of sources, whether the employer can unilaterally order or cancel home work, how the employer assesses the suitability of the job and others.
Keywords: COVID-19; delo na domu; delovna razmerja; delovni čas; delovno pravo; pandemije; Slovenija; varnost pri delu; zdravje pri delu